Spatiotemporal Changes in Heat Stress Index in Iraq (Journal of the College of Basic Education, 2026)
This study analyzes the spatiotemporal trends of human heat stress in Iraq during the period (1980–2024) using the Universal Thermal Climate Index (UTCI), based on hourly data from the ERA5-HEAT dataset. Annual and seasonal minimum, mean, and maximum UTCI values were derived and their trends were examined using the Modified Mann–Kendall (MMK) test and Sen’s slope estimator to quantify rates of change. The results reveal statistically significant increasing trends in most UTCI metrics, indicating a marked intensification of heat stress over the past four decades. The highest rate of increase was observed in the minimum UTCI values (0.62 °C per decade), reflecting an accelerated rise in nighttime warming compared with daytime conditions. Long-term temporal anomalies also show a clear shift toward warmer thermal conditions since the late 1990s. Furthermore, the frequency analysis of UTCI categories indicates a notable decline in cold-stress categories alongside a significant increase in strong, very strong, and extreme heat-stress categories, particularly in daytime maximum conditions. Spatial analysis further demonstrates that the extreme heat-stress category exhibits a consistent upward trend across all meteorological stations, with the highest rates of increase occurring in a belt extending from southwestern to northwestern Iraq, where the rise ranges between 6–10 days per decade. In contrast, the highest annual frequencies of this category are concentrated in central and southern regions, reaching approximately 80–150 days per year. These findings highlight the expanding exposure to extreme thermal conditions and the increasing frequency of severe heat waves in Iraq, underscoring the importance of integrating heat-stress indicators into climate adaptation strategies and sustainable urban planning.